Bacterial survival and distribution during buffy coat platelet production. Issue 4 (19th July 2016) - Taha, M.; Kalab, M.; Yi, Q.‐L.; Maurer, E.; Jenkins, C.; Schubert, P.; Ramirez‐Arcos, S.
Abstract : Background and Objectives: At Canadian Blood Services, buffy coat (BC) platelet concentrates (BC‐PCs) show a generally lower bacterial contamination rate than apheresis PCs. This study investigated whether the PC production method contributes to this observation. Materials and Methods: Whole blood (WB) inoculated with eight bacterial strains was processed using the BC method. Bacteria were enumerated throughout BC‐PC production and subsequent PC storage. Endotoxin production and bacterial adhesion to PC bags were evaluated during PC storage. PC quality was monitored by CD62P expression (flow cytometry) and changes in dynamic light scattering (ThromboLUX ® ). Results: During overnight WB hold, Staphylococcus epidermidis titres remained unchanged, commercial Escherichia coli and Klebsiella pneumoniae were eliminated and the remaining organisms proliferated to high concentrations. Through BC‐PC production, bacteria segregated preferentially towards the cellular fractions compared to plasma ( P < 0·05). During PC storage, most bacteria adhered to the PC bags and Gram negatives produced clinically significant endotoxin levels. Changes in CD62P expression or ThromboLUX scoring did not consistently reflect bacterial contamination in BC‐PCs. Conclusion: WB hold during BC‐PC production does not have a broad‐spectrum bactericidal effect, and therefore, other factors contribute to low rates of contamination in BC‐PCs.